Whistle while you work: an analysis of NHS foundation trust policies. (18th May 2010) - O'Dowd, Adrian; Hayes, Josephine; Cohen, Deborah
Abstract : The ability to raise concerns about a colleague's work is important for patient safety, but Adrian O'Dowd and Josephine Hayes discover that some NHS trusts make it hard